Surface Analysis of 3D (SLM) Co–Cr–W Dental Metallic Materials - Elena-Raluca Baciu; Ramona Cimpoeșu; Anca Vițalariu; Constantin Baciu; Nicanor Cimpoeșu; Alina Sodor; Georgeta Zegan; Alice Murariu (Applied Sciences, 2020)
The surface condition of the materials involved in dentistry is significant for the subsequent operations that are applied in oral cavity. Samples of Co–Cr–W alloy, obtained through selective laser melting (SLM) 3D printing, with different surface states were analyzed. Surface analysis after the 3D printing process and sandblasting was realized from microstructural, chemical composition, profilometry, droplet adhesion, scratch test, and microhardness perspectives. The results presented a hardening process and a roughness modification following the sandblasting procedure, a better adhesion of the liquid droplets, the appearance of micro-cracks during the scratch test, and the oxidation of the sample after the 3D printing process and surface processing.